2000
DOI: 10.1016/s0140-6736(00)02384-9
|View full text |Cite|
|
Sign up to set email alerts
|

Adult cardiovascular risk factors in premature babies

Abstract: Among babies born at term, low birthweight predicts cardiovascular risk factors and disease in adulthood. This study shows that babies born prematurely, whether or not they have intrauterine growth retardation, are predisposed to similar risks as adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
181
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(203 citation statements)
references
References 3 publications
16
181
0
6
Order By: Relevance
“…Similar findings were reported in a study of young adults; a lower GFR, higher serum creatinine and microalbuminaria was reported at 19 years of age in subjects born at <32 weeks gestation (and also small for gestational age) [54]. Furthermore, there is strong epidemiological evidence to link premature birth with the development of hypertension [58][59][60][61][62][63] and increased cardiovascular risk during adulthood [64,65]. This 'risk' may be further exacerbated in the presence of impaired renal function, possibly leading to hypertension, and the possible development of cardiovascular disease in later life [66].…”
Section: Renal Functionsupporting
confidence: 81%
“…Similar findings were reported in a study of young adults; a lower GFR, higher serum creatinine and microalbuminaria was reported at 19 years of age in subjects born at <32 weeks gestation (and also small for gestational age) [54]. Furthermore, there is strong epidemiological evidence to link premature birth with the development of hypertension [58][59][60][61][62][63] and increased cardiovascular risk during adulthood [64,65]. This 'risk' may be further exacerbated in the presence of impaired renal function, possibly leading to hypertension, and the possible development of cardiovascular disease in later life [66].…”
Section: Renal Functionsupporting
confidence: 81%
“…Babies born prematurely also had trends for an adverse metabolic profile and were at risk for hypertension and hyperglycemia as adults. Infants with IUGR were not measurably more disadvantaged than preterm infants with birth weight appropriate for gestational age (Irving et al 2000).…”
Section: The Impact Of Fetal Environment and Prematurity On Adult Heamentioning
confidence: 92%
“…Babies born prematurely, whether or not they have intrauterine growth restriction (IUGR), are also at risk as adults for poor cardiovascular health outcomes (Irving et al 2000). In a study of mothers of 72 LBW and 54 NBW infants born in Edinburgh between November 1973 andFebruary 1975, LBW premature babies had higher adult blood pressure and fasting plasma glucose than NBW controls born at term.…”
Section: The Impact Of Fetal Environment and Prematurity On Adult Heamentioning
confidence: 99%
“…Des anomalies des Ă©preuves fonctionnelles respiratoires persistent Ă  l'Ăąge adulte [11]. 3 Enfants dont le dĂ©veloppement est normal.…”
Section: Revuesunclassified
“…De ce fait, le concept de la programmation pĂ©rinatale dans le contexte de la prĂ©maturitĂ© a Ă©tĂ© dans un premier temps sous-estimĂ©. À la lumiĂšre des donnĂ©es actuelles sur le devenir Ă  long terme de ces enfants, il apparaĂźt clairement que la grande prĂ©maturitĂ© est un facteur de risque, indĂ©pendamment du poids de naissance, de la programmation de maladies chroniques de l'adulte [3]. L'incidence de la prĂ©maturitĂ© et du retard de croissance intra-utĂ©rin tĂ©moigne de l'ampleur des risques liĂ©s Ă  la programmation des maladies chroniques de l'adulte.…”
Section: Revuesunclassified